Dynamic Epicardial Contribution to Cardiac Interstitial c-Kit and Sca1 Cellular Fractions - Pogontke, C.; Guadix, J. A.; Sánchez-Tévar, A. M.; Muñoz-Chápuli, R.; Ruiz-Villalba, A.; Pérez-Pomares, J. M. (Frontiers in Cell and Developmental Biology, 2022)
Background: The cardiac interstitial cellular fraction is composed of multiple cell types. Some of these cells are known to express some well-known stem cell markers such as c-Kit and Sca1, although they are no longer accepted to be true cardiac stem cells. Although their existence in the cardiac interstitium has not been disputed, their dynamic throughout development, specific embryonic origin and potential heterogeneity remain unknown. In this study we hypothesized that both c-KitPOS and Sca1POS cardiac interstitial cell (CIC) subpopulations are related to the Wilms’ tumor 1 (Wt1) epicardial lineage. Methods: In this paper we have used genetic cell lineage tracing methods, immunohistochemistry and FACS techniques to characterize cardiac c-KitPOS and Sca1POS cells. Results: Our data show that approximately 50% of cardiac c-KitPOS cells are derived from the Wt1-lineage at E15.5. This subpopulation decreased along embryonic development, disappearing from P7 onwards. We found that a large proportion of cardiac c-KitPOS cells express specific markers strongly suggesting they are blood-borne cells. On the contrary, the percentage of Sca1POS cells within the Wt1-lineageincrease postnatally. In accordance with these findings, 90% of adult epicardial-derived endothelial cells and 60% of mEFSK4POS cardiac fibroblasts express Sca1. Conclusion: Our study reveals a minor contribution of the Wt1-epicardial lineage to c-KitPOS CIC from embryonic stages to adulthood. Remarkably, a major part of the adult epicardial-derived cell fraction is enriched in Sca1, suggesting that this subpopulation of CICs is heterogeneous from their embryonic origin. The study of this heterogeneity can be instrumental to the development of diagnostic and prognostic tests for the evaluation of cardiac homeostasis and cardiac interstitium response to pathologic stimuli.